Learning Culture in Islamic Boarding Schools: The Exploratory and Confirmatory Factor Analysis - Robin Pratama; Okky Wulandari; Robi Hendra; Siti Amanah (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2021)
This research was intended to test the instrument’s validity with data using exploratory factor analysis (EFA) using SPSS 23.0 to determine the structure and explore the factors in the indicator Learning Culture Variable. Confirmatory Factor Analysis (CFA) First Order was carried out to verify the factorial validity of the Learning Culture construct and to determine the nature of Learning Culture in the context of Islamic Boarding Schools in Jambi City. By using random sampling, a total of 162 samples were taken to test the quality of the instrument from 534 main respondents, namely teachers at Islamic boarding schools in Jambi City who were involved in the main research. This quantitative study used a cross-sectional survey design to analyze the factor structure of the Learning Culture variable. Quantitative data were analyzed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) using SPSS 23 and AMOS 18. The findings of this study are that EFA produces a similar structure from previous studies and this study. The CFA approach verified that the Learning Culture Variable questionnaire was satisfactory for Islamic boarding school teachers in Jambi City, Indonesia. This study explains that establishing validity is an important step for developing a scientific scale for measuring the questionnaire. The construct validity has substantially increased over time and through many previous studies. This scale requires further adjustments to increase the reliability and the ability to explain differences associated with constructs measured in different contexts, cultures and conditions.